Transforming Pendang Lake and its vicinity into a lively community park through the placemaking approach - Mohamad Ramzi, Nurathirah (2018)
The fundamental focus of this study is about transforming Pendang Lake and its vicinity into a lively community park by using placemaking approach. Placemaking concept had been taken as the main process in considering the community itself and the existing feature and activity that need to enhance and conserve to give a new excitement and more communal space for the future. The problem statement that has been a concern on this topic are physical, social space, and ecological connection on-site study. Furthermore, objectives for this problems must be taken to overcome the problems and strengthening the finding result for this project. Primary method and secondary method will become a major tool in this research finding and design process to gain the inventory data by focusing on physical inventory, environmental inventory and socio-cultural inventory. This method will emphasize the concern of community perspective and the sustainability of the study area. Conceptual idea gain from the synthesis method derives the concept of “Nucleus” as the center of activity that relies on the placemaking approach and ecological approach. The finding of this study is showing the result for a lively community park objective which concerns on the needs of the community towards the park. It really important to identify the potential of the park and give new refreshment to the lake as the center of green space and activities for the community. The placemaking approach is the vital method to make a successful community park to serve the community as well as give the identity for the town.